Vector-Borne and Zoonotic Diseases in the Eastern Mediterranean Region: A Systematic Review - Shaffi Fazaludeen Koya; Salma M. Abdalla; Chiori Kodama; Mory Keita; Abdinasir Abubakar (Springer, 2023)
Abstract Background and Objective World Health Organization Eastern Mediterranean Region (WHO EMR) has 40% people in the world in need of humanitarian assistance. This systematic review explores selected vector-borne and zoonotic diseases (VBZDs) of importance to EMR in terms of disease burden across countries and periods, disaggregated across sex, age groups, education levels, income status, and rural/urban areas, related vector or animal source reduction measures, and public health, social and economic impacts and related interventions. Methods We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and reviewed articles in PubMed, Embase, and WHO Global Index Medicus published between 1st of January 2011 and 27th of June 2022. Thirteen VBZDs with at least one reported outbreak in the last five years in the region or prioritized as per previous analysis at the WHO global and regional level and based on expert consultations, were included as part of the analysis. Results The review included 295 studies-55% on leishmaniasis and dengue combined, and 75% studies from Pakistan, Kingdom of Saudi Arabia, and Iran combined. Hospital-based and nationally representative studies constituted 60% and 10% respectively. Males were predominantly affected in most diseases; children reported high burden of Leishmaniasis, whereas elderly had a higher burden of Dengue Fever and Middle East Respiratory Syndrome. Although very few studies reported on socioeconomic differences in burden, the ones that reported showed higher burden of diseases among the disadvantaged socioeconomic groups such as the poor and the less educated. More than 80% studies reported an increase in burden over the years. Conclusion The literature is scanty for most of the diseases reviewed and the number of studies from countries with humanitarian challenges is very low. The need for more nationally representative, population-based studies calls for prioritizing research investments.